Visceral Myopathy Presenting as Acute Appendicitis and Ogilvie Syndrome. (30th April 2013) - Kharbuja, Punyaram; Thakur, Raghvendra; Suo, Jian
Abstract : Background . Visceral myopathy is rare pathological condition of gastrointestinal tract with uncertain clinical presentation and unknown etiology. It often presents with symptoms of chronic intestinal pseudoobstruction of colon. We report a case of visceral myopathy which presented to us as acute appendicitis and Ogilvie syndrome, and we managed it surgically. Method and Result . A case report of 20-year female clinically presented as acute appendicitis and we performed laparoscopic exploration which revealed inflamed appendix with grossly dilated ascending colon. We performed laparoscopic appendectomy and postoperatively managed the patients with IV fluids, antibiotics, neostigmine, and extended length rectal tube for enema and decompression. During postoperative period, she developed abdomen distension and peritonitis, and we ordered abdomen CT which revealed colon pseudo- obstruction. We performed right hemicolectomy with permanent ileostomy, and the histopathology reports of resected colon were visceral myopathy. Conclusion . Visceral myopathy is very rare group of disease and poorly understood condition that may present with chronic or acute intestinal pseudo-obstruction and often mimic other more common gastrointestinal disease. VM should be considered as differential diagnosis whenever the patient presents with acute appendicitis, uncharacteristic abdominal symptoms, recurrent attacks of abdominal distention, and pain with no radiological evidence of intestinal obstruction.